The availability of teaching skills according to information technology among teachers of chemistry in the city of Kirkuk (Journal of the College of Basic Education, 2022)
The aim of the current research is to identify the availability of teaching skills according to information technology among teachers of chemistry in the city of Kirkuk, The research sample consisted of (70) teachers of chemistry who study in the middle school day schools for boys, the scientific branch of the Directorate of Education in Kirkuk Governorate, The researchers used a tool to measure the availability of information technology skills among the members of the research sample, which was represented by the questionnaire and presented to a group of arbitrators, and its psychometric characteristics were extracted, The researchers used a set of statistical methods, including the one-sample t-test, the Pearson correlation coefficient, and the alpha-Kronbach equation, The results showed a good level of teaching skills according to information technology among chemistry teachers, and the research came out with a set of recommendations and suggestions.